ANALYSIS ON THE PULSE STORM EVENT IN THE SOUTH BANDUNG WEST JAVA BASED ON THE TRANSPORTABLE X-BAND DOPLLER RADAR CAMPAIGN, (CASE STUDY : MARCH 16, 2017) - Ginaldi Ari Nugroho; Tiin Sinatra; Trismidianto Trismidianto (Lembaga Penerbangan dan Antariksa Nasional, 2018)
Pulse storm is a term to mention the occurrence of storms that have a short duration with the nature of its weak updraft. The results of the Transportable X-band radar campaign were able to capture a pulse storm at a location 25 km southwest from a radar position. Convective core with echo value > 50 dbz is detected at 4 km altitude but has a weak updraft so that it dissipated in the next 40 minutes. This convective activity is also showed by convective index value as well as Tbb value from Himawari Satellite data in those area. The microburst effect showed from the surface wind shear that expand along + 6.6 km with the edge of the area experiencing high wind with maximum speed from combine shear showed up to 14.5 m/s. The microburst category is dry microburst based on the increase in precipitation value from AWS surface data